Impact of market access and comparative advantage on regional distribution of manufacturing sector - Muhammad Imran; Gu Zhang; HuSen An (China Finance and Economic Review, 2017)
Background: This paper discuss the effects of trade costs and comparative technology on industry location for the economy of China. Methods: The model assumes differences in comparative technology and different intraregional and interregional trade costs, and argues how different factors influence the location of industrial value added. Results: By processing the designed model, equations were set up to check whether the conclusions from our mathematical model are credible under panel data at the provincial level of China from 1995 to 2014. We found that the location of industrial value added in a region strongly related to infrastructure and local market size. Conclusions: Geographical location of a region is an important factor for deciding which factor should be handled first (either intraregional or interregional).
Keywords: 330; New economic geography; Comparative advantage; Market access